Denatured proteins show new vitality: Green synthesis of germanium oxide hollow microspheres with versatile functions by denaturing proteins around bubbles. Issue 1 (1st May 2022) - Zhao, Yanfang; Liang, Xin; Chen, Daoyuan; Bian, Xuhui; Liu, Wanjian; Han, Lei
Abstract: The hollow structure has long attracted great attention because of its excellent properties. However, this special structure is usually synthesized through some complex approaches. Herein, we discovered that denatured bovine serum albumin (BSA) can trigger unusual biomineralization for the simple, green and shape‐controllable synthesis of germanium oxide (GeOx) hollow microsphere (HMS). At high temperature (60°C), BSA was denatured, and a compact BSA layer was formed around the H2 bubbles. The denatured BSA layer was stable and suitable for anchoring and growing GeOx. By simply changing the BSA concentration and temperature, various morphologies of GeOx could be obtained. Due to the denatured protein skeletons and microenvironment‐regulated collapse, GeOx HMS showed great potential for intelligently responsive pesticide delivery in the insect gut, showing superiority over traditional delivery systems, which early release pesticides in the mouth and stomach. Inspired by its large specific surface area, excellent biocompatibility, modifiable functional groups, and high electrocatalytic activity, GeOx HMS was also applied to versatile sensors for H2 O2 assays at physiological pH and rapid coronavirus COVID‐19 detection. This work not only provides some evidence for understanding proteins in depth but also paves a new avenue for the biomineralization‐inspired synthesis of hollow structures with versatile functions. Abstract : Denatured proteins show new vitality for hollow structures with versatile functions. Denatured bovine serum albumin can trigger an unusual biomineralization for the simple, green, and shape‐controllable synthesis of GeOx hollow microsphere (HMS). GeOx HMS shows great application potential for intelligent gut‐targeted pesticide delivery, label‐free COVID‐19 immunosensors, and nonenzymatic H2 O2 sensors under physiological conditions at negative potentials.